2010
DOI: 10.1007/s10826-010-9426-z
|View full text |Cite
|
Sign up to set email alerts
|

The CBCL Bipolar Profile and Attention, Mood, and Behavior Dysregulation

Abstract: Biederman and colleagues reported that a CBCL profile identified youngsters who were diagnosed with bipolar disorder. Some studies found that this CBCL profile does not reliably identify children who present with bipolar disorder, but nonetheless this CBCL does identify youngsters with severe dysfunction. However, the nature of the impairment of youngsters who fit this profile is unclear. The goal of this study was to describe the clinical characteristics of youngsters who fit this CBCL profile. The sample inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…Of increasing scientific interest is the study of DP in population with ADHD (Bellani, Negri, & Brambilla, 2012). Authors suggest a greater likelihood of displaying a DP among ADHD samples compared with other childhood psychiatric disorders (Doerfler, Connor, & Toscano, 2011; Halperin, Rucklidge, Powers, Miller, & Newcorn, 2011; Holtmann, Buchmann, et al, 2011). In addition, children and adolescents with ADHD who show high levels of DP have higher rates of anxiety and disruptive behavior disorders (Spencer et al, 2011) when compared with those with low levels of DP (Biederman, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Of increasing scientific interest is the study of DP in population with ADHD (Bellani, Negri, & Brambilla, 2012). Authors suggest a greater likelihood of displaying a DP among ADHD samples compared with other childhood psychiatric disorders (Doerfler, Connor, & Toscano, 2011; Halperin, Rucklidge, Powers, Miller, & Newcorn, 2011; Holtmann, Buchmann, et al, 2011). In addition, children and adolescents with ADHD who show high levels of DP have higher rates of anxiety and disruptive behavior disorders (Spencer et al, 2011) when compared with those with low levels of DP (Biederman, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical samples, CBCL-DP has been associated with disruptive behaviors, severity of ADHD symptoms, and impaired psychosocial functioning (Doerfler, Connor, & Toscano, 2010;Holtmann et al, 2008;Volk & Todd, 2007. Moreover, this psychometric profile has shown great stability over the childhood years (Boomsma et al, 2006) and has been found to have specific genetic correlates (Doyle et al, 2010;McGough et al, 2008). Notwithstanding its potential utility, the construct measured by CBCL-DP still needs to be clarified, in particular its relationship with the clinical constructs of severe mood dysregulation or temper dysregulation with dysphoria, which characterize patients with severe nonepisodic irritability and hyperarousal (Stringaris et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation has been found to be relatively stable over time, highly heritable (approximately 54%–68% additive genetic factors), and to have fairly substantial shared environmental factors (approximately 18%–30%; Althoff, Rettew, Faraone, Boomsma, & Hudziak, 2006; Boomsma et al, 2006; Hudziak, Althoff, Derks, Faraone, & Boomsma, 2005). Recent studies have also demonstrated positive associations between dysregulation and risk for suicidality (Althoff et al, 2006, 2010; Ayer et al, 2009; Holtmann et al, 2011; Mbekou, Gignac, MacNeil, Mackay, & Renaud, 2014; Volk & Todd, 2007), bipolar disorder (Althoff et al, 2010; Biederman et al, 2009; Diler et al, 2009), aggression (Doerfler, Connor, & Toscano, 2010), oppositional defiant disorder, conduct disorder, attention deficit hyperactivity disorder (Volk & Todd, 2007), anxiety (Althoff et al, 2010), and substance use disorders (Holtmann et al, 2011). Particular combinations of the widely used anxious/depressed, attention, and aggression subscales (AAA; Achenbach, 1991) are often used to index dysregulation because of the associations between elevation on these scales and psychiatric outcomes and impairment (Ayer et al, 2009).…”
mentioning
confidence: 99%